Synergistic B-Al interaction in SBA-15 affording an enhanced activity for the hydro-isomerization of heptane over Pt-B-Al-SBA-15 catalysts - C. Rizescu; B. Cojocaru; N.T. Thanh Hien; P.T.Huyen; V.I. Parvulescu (My University, 2019)
Synergistic B-Al interaction in SBA-15 affording an enhanced activity for the hydro-isomerization of heptane over Pt-B-Al-SBA-15 catalysts
Keywords: B-Al interaction